2017
DOI: 10.1111/epi.13743
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral delivery of the M2 polarizing cytokine interleukin 13 using mesenchymal stem cell implants in a model of temporal lobe epilepsy in mice

Abstract: Our data suggest that MSC-based IL-13 delivery to induce M2 glial activation does not provide any neuroprotective or disease-modifying effects in a mouse model of epilepsy. Moreover, use of cell grafting to deliver bioactive compounds for modulating neuroinflammation may have confounding effects in disease pathology of epilepsy due to the additional immune response generated by the grafted cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…5D-F). Unfortunately, this corroborates many other attempts with genetically modified MSCs (49,63,65,67). Studies that saw an improvement typically saw a change in only one out of multiple assessments, or only looked at a single time point (63,64,66).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…5D-F). Unfortunately, this corroborates many other attempts with genetically modified MSCs (49,63,65,67). Studies that saw an improvement typically saw a change in only one out of multiple assessments, or only looked at a single time point (63,64,66).…”
Section: Discussionsupporting
confidence: 74%
“…SOD2 overexpression demonstrated improved motor coordination at one timepoint tested after focal TBI (64). IL-13 overexpression promotes an M2-like phenotype, but it has only been observed to improve some functional assessments in an SCI model and failed to rescue function in stroke and epilepsy models (65)(66)(67). IL-10 overexpression from MSCs did not reduce TBI lesion volume or improve most functional assessments (47,49).…”
mentioning
confidence: 99%
“…Another study, by inducing SE with a single dose of KA at 10 mg/Kg demonstrated inconsistent chronic epilepsy development, exemplified by only 26% of animals exhibiting >4 seizures/day and the remaining 76% displaying ~0.5 SRS/day [40]. Moreover, many post-SE prototypes have been employed previously in therapeutic efficacy studies once the occurrence of one or a few SRS was recorded [80][81][82][83]. Such investigations are valuable for ascertaining the beneficial effects of promising therapeutic compounds or biologics with an early intervention approach (i.e., application of therapy occurring immediately after the diagnosis of epilepsy or when the epileptogenic processes are still evolving).…”
Section: Discussionmentioning
confidence: 99%
“…Various soluble factors secreted by MSCs, including IL-4 [50], IL-13 [51], prostaglandin E2 (PGE2) [52], and tumor necrosis factor-α-induced gene/protein 6 (TSG-6) [53], have been shown to play a critical role in modulating inflammatory processes and macrophage polarization towards the M2 phenotype in animal models of sepsis [54], acute kidney injury [17], experimental colitis [18], spinal cord injury [19], and skin wounds [1]. To determine the key factors responsible for macrophage polarization towards the M2 phenotype induced by DFSC-CM, we performed a protein array, which revealed that rDFSCs could release many secreted proteins, including immunomodulatory factors, growth factors, cytokines, chemokines and neurotrophic factors, thus providing useful information for future studies.…”
Section: Discussionmentioning
confidence: 99%